2008
DOI: 10.1097/cji.0b013e3181876ab3
|View full text |Cite
|
Sign up to set email alerts
|

An MVA-based Vaccine Targeting the Oncofetal Antigen 5T4 in Patients Undergoing Surgical Resection of Colorectal Cancer Liver Metastases

Abstract: We investigated the use of a therapeutic vaccine, TroVax in patients undergoing surgical resection of colorectal cancer liver metastases. Systemic immunity generated by vaccination before and after resection of metastases was measured in addition to assessing safety and analyzing the function and phenotype of tumor-associated lymphocytes. Twenty patients were scheduled to receive 2 TroVax vaccinations at 2-week intervals preoperatively and 2 postoperatively; if immune responses were detected, 2 further vaccina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
36
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 31 publications
1
36
0
Order By: Relevance
“…Results from phase I and II clinical studies of MVA-5T4 in renal, colorectal, and prostate cancer patients were encouraging and showed that immune responses were induced in almost all treated patients, and associations between 5T4-specific cellular or humoral responses and clinical benefit were reported in seven of nine studies (8)(9)(10)(11)(12)(13)(14)(15)(16). In particular, studies in RCC and colorectal cancer patients have detected an association between 5T4-specific (but not MVA) antibody responses and enhanced survival (9,12,16).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Results from phase I and II clinical studies of MVA-5T4 in renal, colorectal, and prostate cancer patients were encouraging and showed that immune responses were induced in almost all treated patients, and associations between 5T4-specific cellular or humoral responses and clinical benefit were reported in seven of nine studies (8)(9)(10)(11)(12)(13)(14)(15)(16). In particular, studies in RCC and colorectal cancer patients have detected an association between 5T4-specific (but not MVA) antibody responses and enhanced survival (9,12,16).…”
Section: Discussionmentioning
confidence: 96%
“…These studies showed MVA-5T4 to be well tolerated and able to induce 5T4-specific immune responses in most patients. Furthermore, associations between 5T4-specific cellular or humoral responses and clinical benefit were reported in seven of the nine studies (8)(9)(10)(11)(12)(13)(14)(15)(16).…”
mentioning
confidence: 96%
“…The possible induction of antitumor-specific lymphocytes by CTLA4 blockade requires further investigation in man, but may suggest a rationale for combining anti-CTLA4 blockade with one of the antigen-targeted therapies currently in clinical development, such as CEA or 5T4 vaccination (27,40), 5T4 superantigen (41), or CEA-targeted cytotoxic T cells. CTLA4 blockade has previously been administered to melanoma and ovarian cancer patients who had received vaccination with antitumor immunity being shown (42).…”
Section: Discussionmentioning
confidence: 99%
“…To explore changes in in vitro responses to relevant TAAs, overlapping 5T4 32-mer peptides (18 patients, 24 cycles) and purified CEA (13 patients, 15 cycles) were used in a thymidine incorporation proliferation assay (26). All time points for each patient were investigated in the same assay: cryopreserved PBMCs were thawed and 1.5 × 10 5 viable cells per well were cultured in Iscove's modified Dulbecco's medium with 10% AB serum, with six pools of four overlapping 5T4 peptides (defined as A-X) spanning the whole sequence of human 5T4 (10 μg/mL of each peptide); media controls with and without the appropriate concentration of dimethyl sulfoxide were used to prepare peptide stocks (27,28). In parallel assays, PBMCs were cultured with purified CEA (Calbiochem) at 100, 200, and, if sufficient cells are present, 300 ng/mL.…”
Section: Translational Relevancementioning
confidence: 99%
See 1 more Smart Citation